Advancements and approaches towards moving from legacy application to cloud. (2016) - Rai, Rashmi; Sahoo, G.; Mehfuz, Shabana
With advancements in cloud services offering suppler and cost efficient solutions to support the IT infrastructure and business applications, a large number of legacy systems are steadily making a move. However, these migrations are often performed in ad hoc manner leading to underutilisation of the technology. As a result of which lot of research is going on in this area to formalise the cloud migration process. The main objective of this work is to highlight and consolidate the recent advancements that have taken place while moving from legacy systems to cloud. Work also includes advancements in virtual machine migration which makes it unique. Another contribution is a proposed conceptual model for migrating old applications to the cloud based on existing solutions. Our work concludes that the research in the area of cloud migration is evolving at a steady pace and has tremendous potential for further research and advancements both for industry and academia.